Implementasi RFID dan NodeMCU Untuk Data Kunjungan Perpustakaan Berbasis IoT - Khadafi, Amri Yahya; Darussalam, Ucuk; Winarsih, Winarsih (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Radio Frequency Identification (RFID), automatic identification by storing and sending data wirelessly via RFID card or transponders. A variety of recent applications of RFID have been developed in various sectors of life, especially related to identification via radio waves both in the field of automotive, biomedical, educational institutions, police, banks, transportation, and others. The purpose of this research is to design an RFID application in the field of libraries, so that RFID can be used as an alternative solution other than the barcode as the media identification data stored neatly in a book database program through the support of electromagnetic waves. At present we know that the national university library still uses paper to fill in the visit, to resolve the issue data from testing using the RFID method and the NodeMCU microcontroller, it can send data to a web application and can be stored in a database, It is expected that from the results of testing this application can solve the problems that exist in the library that previously members wrote a visit data to enter the future only need to tap the card to enter and do not need paper as a registration medium